2005
DOI: 10.1159/000084821
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Treatment with Irinotecan and Raltitrexed in Metastatic Colorectal Cancer

Abstract: Objectives: The combination of irinotecan and raltitrexed is safe and active in 5-fluorouracil-refractory, metastatic colorectal cancer (CRC), with the advantage of its convenient three-weekly schedule. The aim of this multicenter phase II study was to assess its efficacy and toxicity in first-line treatment. Methods: Between May 2000 and March 2001, 62 previously untreated patients received irinotecan (350 mg/m2) plus raltitrexed (3 mg/m2), with courses repeated every 21 days. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…On the basis of the predefined eligibility criteria, we selected 12 studies [3][4][5][7][8][9][10][11][12][13][14][15] that fulfilled the qualitative and quantitative requirements of the systematic analysis. A total of 735 patients were enrolled across the selected trials (range, 37-94).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the predefined eligibility criteria, we selected 12 studies [3][4][5][7][8][9][10][11][12][13][14][15] that fulfilled the qualitative and quantitative requirements of the systematic analysis. A total of 735 patients were enrolled across the selected trials (range, 37-94).…”
Section: Resultsmentioning
confidence: 99%
“…Aparicio et al [7] Carnaghi et al [4] Cascinu et al [3] Chiara et al [8] Feliu et al [10] Feliu et al [9] TOMIRI Feliu et al [9] TOMOX Gravalos et al [5] Martoni et al [11] Neri et al [12] Santini et al [13] Seitz et al [15] Scheithauer et al [14] 0 required, unlike fluoropyrimidines [1]. In addition, results reported at the American Society of Clinical Oncology meeting in 2000 suggest that the prophylactic use of the 5-HT3 antagonist ondansetron reduces the severity of nausea and diarrhea, preventing dehydration, and the use of dexamethasone reduces the incidence of fever and fatigue [23].…”
Section: Lower Limitmentioning
confidence: 99%
“…RIR as an active regimen in gastrointestinal malignancies has been demonstrated in a phase I clinical and pharmacogenetic trial [11]. Other published single-arm studies also considered RIR as a suboptimal e cient schedule at the expense of moderate toxicity for patients with metastatic CRC in rst-or secondline treatment [12][13][14]. Moreover, a randomized phase II study compared RIR with raltitrexed alone as second-line treatment in patients with gemcitabine-pretreated advanced pancreatic adenocarcinoma and also indicated that the combination therapy with superior survival [15].…”
Section: Discussionmentioning
confidence: 99%
“…Grade 3/4 leukopenia occurred in 5 (13.15%) patients. According to previous reports, most studies used 300-350 mg/m 2 irinotecan in the treatment of colorectal cancer [28,29]. A lower dose of irinotecan (200mg/m 2 ) combined with raltitrexed was administered to treat patients with advanced pancreatic adenocarcinoma from a randomized multicenter phase II study [19].…”
Section: Discussionmentioning
confidence: 99%